A SKETSA GERAKAN PEMBARUAN ISLAM DI INDONESIA: Studi Kritis terhadap Pemikiran Harun Nasution - Muhlis, Muhammad (LP2M Institut Agama Islam Nurul Hakim, 2022)
This study tries to analyze the views in particular about Islamic renewal. Realizing that Islamic renewal aims to realize a civilized Islam as the efforts of Islamic thinkers both past and present. Various views on Islamic renewal have been put forward by experts. The principle is that reform in Islam is something urgent to bridge the decline of Islam towards progress and civilization itself. Various problems and dynamics of Islamic education, especially in a time that is currently growing with various scientific achievements developing so dynamically. So, besides being urgent, Islamic renewal is also immediately realized in order to achieve progress as was achieved during the caliphate at that time so that it is known as the golden age of the golden age. So from here we will find the derivation and various views of figures about renewal. Some say that renewal is another name for modernization. Is it true, then in this research, we try to find out about the nature of renewal and modernization in Islam, especially since it cannot be separated from the efforts of a movement.